2021
DOI: 10.1103/physrevlett.126.088102
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivelike Motions in a Solvent-Free Protein-Polymer Hybrid

Abstract: The interaction between proteins and hydration water stabilizes protein structure and promotes functional dynamics, with water translational motions enabling protein flexibility. Engineered solvent-free proteinpolymer hybrids have been shown to preserve protein structure, function, and dynamics. Here, we used neutron scattering, protein and polymer perdeuteration, and molecular dynamics simulations to explore how a polymer dynamically replaces water. Even though relaxation rates and vibrational properties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Hence a clear understanding of the microscopic behaviour of substrates in the SFPL is needed for the progress of this exotic eld. Although many experiments and a few molecular dynamics simulations [24][25][26] have been reported on various SFPLs, the microscopic behavior of substrates in such liquids is yet to be Chemistry and Physics of Materials Unit, Jawaharlal Nehru Centre for Advanced Scientic Research, Bangalore 560 064, India. E-mail: bala@jncasr.ac.in † Electronic supplementary information (ESI) available: ESI text and gures in a PDF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence a clear understanding of the microscopic behaviour of substrates in the SFPL is needed for the progress of this exotic eld. Although many experiments and a few molecular dynamics simulations [24][25][26] have been reported on various SFPLs, the microscopic behavior of substrates in such liquids is yet to be Chemistry and Physics of Materials Unit, Jawaharlal Nehru Centre for Advanced Scientic Research, Bangalore 560 064, India. E-mail: bala@jncasr.ac.in † Electronic supplementary information (ESI) available: ESI text and gures in a PDF.…”
Section: Introductionmentioning
confidence: 99%
“…Hence a clear understanding of the microscopic behaviour of substrates in the SFPL is needed for the progress of this exotic field. Although many experiments and a few molecular dynamics simulations 24–26 have been reported on various SFPLs, the microscopic behavior of substrates in such liquids is yet to be investigated. The questions which need investigations are: (i) how much conformational flexibility do substrates have in the SFPL?…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that discrete hybrid macromolecules comprising electrostatically stabilized protein–polymer surfactant nanoconjugates with well-defined stoichiometries can be used to generate a raft of biologically active materials with emergent properties. For example, the bioconjugates can be dehydrated to produce solvent-free liquid proteins with oxygen-binding properties, hierarchically self-assembled to produce porous membranes with recyclable catalytic activity, or partitioned into hydrophobic cell membrane domains to yield artificial membrane-binding proteins. Significantly, the proteins in these hybrid materials are folded, biologically active, hyper-thermostable ( T m = 155 °C), and have protein dynamics that closely resembled those of fully hydrated proteins. Moreover, using this approach, we developed a new self-contained enzymatic biofluid, where lipases were re-engineered to produce room temperature liquids that required no dispersion medium, could solubilize substrates, and catalyze the hydrolysis of fatty acid esters up to temperatures of 150 °C …”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Significantly, the proteins in these hybrid materials are folded, biologically active, hyper-thermostable ( T m = 155 °C), 9 and have protein dynamics that closely resembled those of fully hydrated proteins. 10 12 Moreover, using this approach, we developed a new self-contained enzymatic biofluid, where lipases were re-engineered to produce room temperature liquids that required no dispersion medium, could solubilize substrates, and catalyze the hydrolysis of fatty acid esters up to temperatures of 150 °C. 13 …”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9][10][11] Water in this region experiences slow, distinct dynamics compared to bulk water. 8 Many techniques, including NMR, 12,13 neutron scattering, 14,15 laser spectroscopies, 9,16 and molecular dynamics simulations (MD) 11,17,18 have studied the hydration layer water molecules at different time and length scales and have sought to clarify the essential nature of the hydration layers and their interactions with protein dynamics.…”
Section: Introductionmentioning
confidence: 99%